Cardiovascular health and resilience to cognitive decline and impairment among diverse Hispanics/Latinos: Results from the Study of Latinos‐ Investigation of Neurocognitive Aging (SOL‐INCA). (20th December 2022) - Tarraf, Wassim; Stickel, Ariana M; Wu, Benson; Brewer, James B.; Gallo, Linda C; Talavera, Gregory A; Isasi, Carmen R; Kaplan, Robert; Lipton, Richard B.; Daviglus, Martha L; Zeng, Donglin; Pike, James R.; et al.
Abstract: Background: Cardiovascular disease contributes to cognitive impairment and dementia, particularly among populations facing health disparities. However, the long‐term effects of cardiovascular health on later cognitive health have not been examined among Hispanics/Latinos. Therefore, we examined relationships between cardiovascular health with change in cognition and mild cognitive impairment (MCI) among diverse Hispanics/Latinos. Method: Hispanics/Latinos (n = 6, 223, ages 50‐86 years) were enrolled in the Study of Latinos ‐ Investigation of Neurocognitive Aging (SOL‐INCA), an ancillary study of the Hispanic Community Health Study/SOL (HCHS/SOL). Cardiovascular health was the primary exposure, measured using the American Heart Association's Life's Simple 7s (LS7). Outcomes of interest included 7‐year performance in cognition, change in cognition, and MCI prevalence. Cognitive outcomes included measures of learning and memory, verbal fluency, executive functioning and processing speed, and a global composite (average of the z‐scores on each test). Survey linear regressions were used to separately model the associations between LS7 with outcomes of interest, controlling for age, age2, education, language preference, Hispanic/Latino background, and income. Results: Better cardiovascular health (higher LS7 Score) was associated with higher global cognitive performance (βGlobal = 0.028 [SE = 0.005], p<0.001). These associations were evident in learning (βB‐SEVLT‐Sum = 0.024 [SE = 0.007], p<0.01), memory (β = 0.024B‐SEVLT‐Recall [SE = 0.008], p<0.01), verbal fluency (β = 0.039WF [SE = 0.008], p<0.001), executive functioning and processing speed (βDSS = 0.027 [SE = 0.007], p<0.001 and βTrails A = ‐0.022 [SE = 0.007], p<0.01). We also observed significant associations between better cardiovascular health and improved global cognitive change (β = 0.023 [SE = 0.008], p<0.01), evident also for learning (βB‐SEVLT‐Sum = 0.017 [SE = 0.008], p<0.05), executive functioning and processing speed (βDSS = 0.034 [SE = 0.008], p<0.001). Lastly, better cardiovascular health decreased the odds ratios for prevalent MCI (ORMCI = 0.90 [0.842, 0.959], p<0.01). Conclusion: Cardiovascular health was protective of 7‐year cognitive aging and associated with reduced MCI prevalence. Our findings suggest that cardiovascular health may improve resilience to cognitive decline and impairment amongst diverse Hispanics/Latinos, which could prove instrumental in public health efforts for reducing dementia disparities facing Hispanics/Latinos.